"Pleasantville" y los códigos del color - Castellanos Rodríguez, Belén (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this paper about the film Pleasantville, we intend to highlight the importance of aesthetic-perceptual transformations as the engine of political awareness, highlighting the transition from black and white to multicolor in movies and on television as the main theme of the film. We deal with the question of the contemporary and built character of the memories, the past and history, and the introjection of technological innovations in the imagination that we put in place for such a productive task.
Keywords: image; film and television; black and white; color; Pleasentville; synchrony; past; present; memories; memory; language cinema